Distinct Role of von Willebrand Factor Triplet Bands in Glycoprotein Ib-Dependent Platelet Adhesion and Thrombus Formation under Flow - Fuchs, Birte; de Witt, Susanne; Solecka, Barbara A.; Kröning, Mario; Obser, Tobias; Cosemans, Judith M. E. M.; Schneppenheim, Reinhard; Heemskerk, Johan W. M.; Kannicht, Christoph (Seminars in Thrombosis and Hemostasis, 2013)
Multimeric glycoprotein von Willebrand factor (VWF) exhibits a unique triplet structure of individual oligomers, resulting from ADAMTS-13 (a disintegrin and metalloproteinase with thrombospondin type 1 motifs 13) cleavage. The faster and slower migrating triplet bands of a given VWF multimer have one shorter or longer N-terminal peptide sequence, respectively. Within this peptide sequence, the A1 domain regulates interaction of VWF with platelet glycoprotein (GP)Ib. Therefore, platelet-adhesive properties of two VWF preparations with similar multimeric distribution but different triplet composition were investigated for differential functional activities. Preparation A was enriched in intermediate triplet bands, whereas preparation B predominantly contained larger triplet bands. Binding studies revealed that preparation A displayed a reduced affinity for recombinant GPIb but an unchanged affinity for collagen type III when compared to preparation B. Under high-shear flow conditions, preparation A was less active in recruiting platelets to collagen type III. Furthermore, when added to blood from patients with von Willebrand disease (VWD), defective thrombus formation was less restored. Thus, VWF forms lacking larger-size triplet bands appear to have a decreased potential to recruit platelets to collagen-bound VWF under arterial flow conditions. By implication, changes in triplet band distribution observed in patients with VWD may result in altered platelet adhesion at high-shear flow.
Keywords: collagen; flow; glycoprotein Ib; von Willebrand factor triplets; platelet adhesion